Employee Construct of Work-Values among University Support-Staff - Odunaike, Bolawale Abayomi; Babalola, Sunday Samson (Journal of Reviews on Global Economics, 2019)
Work-values of employees often determine the attitude and disposition that they are likely to display, while discharging their daily duties. In addition to the extrinsic and intrinsic values attached to work by employees in organisations, social factors, such as family roles and responsibilities are also major determinant of how people conceive their jobs and tasks allocated to them. In essence, the conception that workers have about their jobs affect their level of commitment and performance. This study examined employees’ construction of work-values. Specifically, the study highlighted work-values of staff in terms of gender, cadre and profession constructs. The self-determination theory explained the theoretical underpinnings the study. The research design was descriptive which relied on quantitative and qualitative research methods. A total of 312 questionnaires were administered and twenty-four in-depth interview conducted in six clustered departments. Qualitative and quantitative data were analysed using NVIVO and IBM_SPSS. The study submitted that staff’s construct of work-values varied with regards to gender, cadre, and professions. Married female employees preferred the intrinsic part of their job, such as convenience, autonomy, and hours spent at work which allowed them to attend to their domestic roles of a wife and mother. The majority of the junior cadre conceived job security as illusionary, thereby, making them extrinsically oriented, however, work-values varied among the professions, which were clustered along departmental lines.